Peran Kepala Sekolah dalam Menumbuhkan Budaya Anti Korupsi di Lingkungan Sekolah - Juwono, Hendro (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2025)
Corruption is one of the crucial problems that threatens the sustainability of national development and damages the values ​​of national life. Education is seen as a strategic instrument in forming an anti-corruption character from an early age, with schools as the vanguard in this effort. This study aims to describe the role of school principals in fostering an anti-corruption culture in the school environment. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. The results of the study indicate that school principals have a central role in forming an anti-corruption culture, which is reflected in three main functions: as policy makers who establish rules and programs based on integrity values; as educators who instill and provide examples of anti-corruption attitudes to school residents; and as evaluators who routinely assess the effectiveness of anti-corruption programs and practices in schools. These three roles work synergistically in creating a clean, transparent, and integrity-based school environment. Therefore, strengthening the capacity of school principals to carry out these roles is very important to support the national movement to eradicate corruption through education.